The use of community language learning (CLL) method to enhance the students' english speaking of AMIK Medicom Medan - Rani Rakasiwi; Masriani Mery Rosmida Silalahi; Marlina Tampubolon; Ricky Asi Erwindo Siahaan (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
This study deals with The Use of Community Language Learning (CLL) Method to Enhance the students' English speaking of AMIK Medicom Medan. The objectives of this research were to The Use of Community Language Learning (CLL) Method to Enhance the students' English speaking of AMIK Medicom Medan. Descriptive qualitative method was applied in this study. The data of this study were the utterances of students in interview with total number 30 students during conversation class. Data will be analyzed using the method of Miles, Huberman & Saldana (2014: 33). CLL had good result of students’ learning and can enhance students’ English speaking at AMIK Medicom Medan. Furthermore, CLL has been given positive response to students. In addition, there were innovations that were dynamic, flexible and creative.